Filosifis dalam Acara Kuda Lumping - Edi Sumanto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
The purpose of this study was to determine the philosophy contained in the activities of the Kuda Lumping event. The type of research used is the library research method. The results showed that the activities at the Kuda Lumping art event were a form of traditional art that existed in our country from the many popular arts and cultural activities that featured various kinds of decorations such as soldiers riding a piggyback which is often called a braid horse that uses gamelan music and dances. drum (song). The conclusion of this research is Kuda Lumping is an ancient art form that contains certain meanings that can be understood by people who understand the event, because the Kuda Lumping event contains many philosophical values ​​in its activities, such as sosial values, religious values ​​and the embodiment of the intensity of heroism and the military field. cavalry. Keywords: Horse, Lumping, Philosophy.